Designing Cassegrain Telescope System with Best Obscuration Ratio of Secondary Mirror - Foadi, Raad Falih Hassan; Ahmed, Ahmed Kamil (Iraqi Journal of Science, 2023)
A computer simulation was conducted using Optics Software for Layout and Optimization (OSLO) to design a Cassegrain telescope system for on-axis rays. In order to establish such a telescope, the two mirrors of the optical system were designed as spherical surfaces: a concave mirror and a convex mirror. The obscuration ratios of the Cassegrain telescope's secondary mirror were examined using different values, which ranged between 0.1 and 0.3, to determine the best obscuration ratio. This work adopted three criteria to decide which obscuration ratio is the best for the Cassegrain telescope. The first criterion was the number of rays that reached the final image. The second criterion was calculating the modulation transfer function (MTF). The third criterion was calculating the point spread function (PSF) and Strehl ratio (SR). Finally, the result showed that the best obscuration ratio of the telescope’s secondary mirror was found at D2/D1=0.116-0.166, where D1=0.76 m for the primary mirror and D2=0.09 – 0.125m for the secondary mirror.